Optimalisasi Nilai Produk Melalui Manajemen Usaha, Kemasan, Dan Labeling Desa Burai - Novalia, Nurkardina; Maulana, Ahmad; Rosa, Aslamia; Putri, Melisa Ariani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service activity aims to improve the ability of MSME actors in Burai Village through training and coaching in the fields of production, business management, and the use of good packaging and labeling. Methodology/approach: The approach used in implementing community service involves providing support to meet needs through assistance and education. The methods employed included lectures, demonstrations, and mentoring. Results/findings: usiness management is not yet fully optimized, which limits the effectiveness of business operations. Additionally, products such as wet cakes and kemplang lack proper packaging, which could enhance their appeal. Furthermore, the absence of effective labeling has led to poor product recognition among consumers. Conclusions: The conclusion drawn from the findings is that while the home industry has adequate facilities, it faces challenges in business management, packaging, and labeling, which hinder product appeal and recognition. Addressing these issues through training and support can enhance the development and growth of MSMEs in the home industry sector. Limitations: While the home industry owners have adequate facilities and infrastructure, they remain underdeveloped in terms of business management, packaging, and labeling. Contribution: This program aims to offer training and support to address issues related to management, packaging, and labeling, thereby enhancing MSMEs' capabilities to grow their businesses in the home industry sector. This activity is supported by Sriwijaya University's community service grant as a practical demonstration of community engagement.